2008
DOI: 10.1016/j.econlet.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Productivity spillovers through vertical linkages: Evidence from 17 OECD countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Most of the identified studies, although related to the FDI spillover literature, did not estimate vertical spillovers. We also excluded a few studies that estimated vertical spillovers but did not define linkages as a ratio and thus could not be used to compute the semi-elasticity (for example, Kugler 2006;Bitzer et al, 2008). We often had to ask the authors for sample means of linkage variables or for clarification of their methodology: about 20% of the studies could only be included thanks to cooperation from the authors.…”
Section: The Spillover Estimates Data Setmentioning
confidence: 98%
“…Most of the identified studies, although related to the FDI spillover literature, did not estimate vertical spillovers. We also excluded a few studies that estimated vertical spillovers but did not define linkages as a ratio and thus could not be used to compute the semi-elasticity (for example, Kugler 2006;Bitzer et al, 2008). We often had to ask the authors for sample means of linkage variables or for clarification of their methodology: about 20% of the studies could only be included thanks to cooperation from the authors.…”
Section: The Spillover Estimates Data Setmentioning
confidence: 98%
“…Wang and Gu (2006) have examined the effect of FDI on total factor productivity (TFP) growth in Canadian manufacturing industries over the period 1973-1977 and found that FDI generates strong and positive spillover effects on TFP growth through both backward and forward linkages. Bitzer et al (2007) have considered the effect of horizontal and vertical spillovers through industry-level data for 17 OECD and Central and Eastern European countries (CEEC), demonstrating evidence of positive spillovers through vertical backward linkages, but with much higher effect for CEEC. They also found that the effect of horizontal linkages is positive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…research is for the year 2000. As a result, this study holds the linkage coefficients for vertical spillovers constant over the observation period, as done by Bitzer et al (2008). Following Javorcik (2004), Blalock and Gertler (2008), Le andPomfret (2011), andSuyanto et al (2014), backward linkages are defined as follows:…”
Section: Model Specificationmentioning
confidence: 99%